Ajustamentos alocativos no mercado de trabalho brasileiro (2012-2017) - Piacenti, Samara Cristina Vieceli (2020)
Mobile factors of production (labor and capital) are attracted by the centripetal forces of expanding regions, in order to contribute to their development. Literature largely associates the spatial location of economic activities with agglomeration economies. Workers can exhibit allocative behavior between economic activities, such in space, where their magnitude is increased in periods of economic instability. In the face of the macroeconomic and idiosyncratic shock of the Brazilian economy in 2014, this study aims to analyze the allocative adjustments in the labor market of Brazilian municipalities in the period from 2012 to 2017, a period of crisis and subsequent economic stagnation. To achieve the objective, three methodologies were used: i) labor market turbulence index, separated into four sectors (industry; commerce and services; public administration; and agriculture); ii) Exploratory Analysis of Spatial Data (EASD), using Moran's I and LISA cluster map; and iii) econometric regression of spatial data panel. The results show that the Brazilian labor market is going through a process of deglomeration of the major development poles. Agglomerations are moving towards secondary regional poles in the hierarchy of development poles. In this scenario of structural changes in the labor market facing recession, the sectors of economic activity that most contributed attracting labor were public administration and agriculture, while the sectors of industry, commerce and services showed greater number of dismissals than employment generation. Brazilian economic growth and, consequently, the adjustment of the labor market are slowly recovering from the impacts caused by this shock. It indicates that a low dynamism in the activities of the market is not favoring a consistent recovery of the Brazilian economy.